Alf Ross on Practical Reason - ZALUSKI, Wojciech (Utopía y Praxis Latinoamericana, 2016)
In his early work Kritik der Sogenannten Â Praktischen Erkenntnis. Zugleich Prolegomena zuÂ Einer Kritik der Rechtswissenschaft the eminent DanishÂ legal philosopher Alf Ross intended to provide theÂ philosophical foundations for the construction of hisÂ theory of law. The central element of these foundationsÂ is his critique of practical reason (practical cognition).Â The purpose of this paper is to evaluate this critique. It isÂ argued that in his analysis Ross oscillates between twoÂ different understandings of practical reason. AccordingÂ to the first one, practical reason is a special capacityÂ to cognize and establish the objectively existing moralÂ norms (values, or ends); according to the second one,Â it is a special capacity just to cognize the objectivelyÂ existing moral norms (values, or ends). It is argued that his most interesting and plausible arguments (pointingÂ at logical inconsistencies) against practical reason applyÂ only to the former understanding thereof, not to theÂ latter. Accordingly, his work fails to provide conclusiveÂ reasons for rejecting the concept of practical reason asÂ a special capacity for the cognition of the objectivelyÂ existing moral norms (values, or ends).